Student satisfaction in professional training in the area of Science, Technology and Environment - Castillo Martínez, Jamill; Artola García, Javier Osmar (Revista Universitaria del Caribe, 2023)
URACCAN as a Higher Education institution is immersed in professional quality, reason why it researched student satisfaction in professional training in Science, Technology and Environment at Las Minas Campus and its extensions in the Northern Caribbean of Nicaragua. The dimensions evaluated were the level of satisfaction with the coordination management of their professional training, planning and development of subjects concerning their professional profile, teaching work in the quality of their professional training and planning and development of practices in their professional training through a mixed study with a Likert scale and in-depth group interviews. The main findings show that 68.66% of the students show general satisfaction with the coordination management. For its part, the Veterinary Medicine career has the highest satisfaction with 89.99% and the Agroforestry Engineering career has the lowest satisfaction with 59.95%. Regarding the planning and development of the subjects based on the professional profile, the general satisfaction of the students is 75.33%, with the Veterinary Medicine career being the highest satisfied with 96.02% and Agroforestry Engineering with the lowest satisfaction of 69.58%. 86.96% of the students are satisfied with the work of the teaching staff in relation to the development of the practices, 71.83% of the students are satisfied with the development of the practices in their degree, however, the Agroforestry Engineering degree reaches 49.8%.